2012
DOI: 10.1080/01973533.2012.711692
|View full text |Cite
|
Sign up to set email alerts
|

The Ethics of “Smart Drugs”: Moral Judgments About Healthy People's Use of Cognitive-Enhancing Drugs

Abstract: What issues matter when people judge whether it is morally objectionable for healthy people to use cognitive-enhancing (CE) drugs? Two studies surveyed university students regarding the following concerns: Health, competitive fairness, distributive fairness, peer pressure, naturalness and dosage form. Participants condemned CE drug use when there were long-term negative effects on health, and when CE drug use was seen to provide an unfair advantage to someone in an exam situation while others were not taking t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 30 publications
5
65
0
Order By: Relevance
“…If this is the case, using PCEs to improve academic performance could lead to even more disparities in academic attainment. A recent survey of University of Cambridge students indicated that students are opposed to using PCEs because of the potential risks that they might cause to healthy individuals and the inequality of access which might lead to disparity in academic performance . These views were similar to Australian students who expressed strong objections to the uses of these drugs in academic contexts …”
Section: Distributive Justice and Competitive Fairnessmentioning
confidence: 99%
“…If this is the case, using PCEs to improve academic performance could lead to even more disparities in academic attainment. A recent survey of University of Cambridge students indicated that students are opposed to using PCEs because of the potential risks that they might cause to healthy individuals and the inequality of access which might lead to disparity in academic performance . These views were similar to Australian students who expressed strong objections to the uses of these drugs in academic contexts …”
Section: Distributive Justice and Competitive Fairnessmentioning
confidence: 99%
“…Furthermore, people morally object more to the application of PCE substances if they are artificial rather than natural, and if they are taken in the form of injections rather than pills (Scheske and Schnall, 2012). Focus group participants in the Netherlands referred to natural remedies, placebo, and psychological treatment as alternatives to a specific example of PCE (taking β-blockers during a driving test; Asscher and Schermer, 2013).…”
Section: Medical Safetymentioning
confidence: 99%
“…Scheske and Schnall (2012) showed that the use of PCE substances is perceived as more wrong if not everybody can afford them, compared to situations in which everybody can. Fitz et al (2013) investigated fairness by using the contrastive vignette technique online.…”
Section: Fairnessmentioning
confidence: 99%
“…To measure perceived health and safety concerns, we used a 3-item measure from Scheske and Schnall (2012). Participants were asked what they thought of healthy students using cognitive enhancers to increase mental performance if there are (a) no negative side effects on health, (b) temporary negative side effects on health, and (c) long-term negative side effects on health, and responded on a scale from 0 (perfectly OK) to 10 (extremely wrong).…”
Section: Attitudes Toward Cognitive Enhancersmentioning
confidence: 99%